Recent Trends in U.S. Earnings Inequality by Gender - Jacobsen, Joyce P. (Journal of Income Distribution®, 2003)
This paper presents an overview of recent trends in U.S. earnings inequality with a focus on gender differences. Data from the 1980, 1990, and 2000 Censuses are used. Earnings and per capita household income inequality measures have risen from 1980 to 2000, both overall and among women and men separately. Theil index decompositions illustrate that within-gender inequality is rising. Simulations that treat women “more like men” in the labor market raise women’s earnings relative to men but also have the effect of increasing within-gender inequality for women.